Nannoplankton Assemblage Succession Throughout Cretaceous/ Tertiary Boundary in the âPâ Well Section, Santos Basin, Brazil - Panuju, Panuju (Geological Agency, 2011)
DOI:Â 10.17014/ijog.v6i1.115The massive change in calcareous nannoplankton assemblages throughout Cretaceous/Tertiary (K/T) boundary (65.5 M.a.) has been illustrated by several authors. The diverse and abundant assemblage disappears suddenly above the Cretaceous/Tertiary boundary. This event is related to the most dramatic environmentalÂ changes in the Earths history due to the catastrophic events, those are meteorite impact (Chicxulub) and supervolcano eruption (Deccan) occurring at the end of Cretaceous. The succeeding age was a time of rapid evolution of nannoplankton during Paleocene. A quantitative method analysis of nannoplankton throughoutÂ Maastrichtian to Paleocene of âPâ well section, Santos Basin, Brazil, indicated that the nannoplankton assemblages abruptly decrease in diversity and abundance and mostly change in species composition. The various complex shapes of species at Maastrichtian also underwent changing to simple plain shapes and small at Paleocene. The sedimentary section ranges from the top of zone CC23 (Coccolith Cretaceous 23) to NP9 (Nannoplankton Paleogen 9). It is bounded by the Last Occurrence (LO) of Tranolithus pachelosusÂ at the base and Fasciculithus tympaniformis at the top. The biostratigraphic discontinuity characterizedÂ by the absence of zone CC26 to NP4 is an indicator for the presence of an unconformity at K/T boundary within analyzed section. The Cretaceous nannoplankton assemblages are dominated by Genera Watznaueria, Micula, Arkhangelskiella, Cribrosphaerella, Eiffellithus, Predicosphaera, and Retecapsa, whilst the Paleocene assemblages are dominated by Genera Toweius, Ericsonia, and Coccolithus. Survivor Cretaceous species recovered into Tertiary sediments consist of Braarudosphaera bigelowii, Biscutum melaniae, Neocrepidolithus neocrassus, Placozygus sigmoides, Cyclagelosaphaera reinhardtii, Markalius inversus, and Scapolithus fossilis.